Niefortunność komunikacyjna relacji nauczyciel – uczeń we współczesnych powieściach dla młodzieży - Burska-Ratajczyk, Beata (Dydaktyka Polonistyczna, 2019)
The aim of the research was to try to answer the question about the literary picture of communication disorders in the school environment. The analysis shows that in contemporary novels for young people it is not difficult to find the examples of teachers violating the basic rules of conversation both in the process of education and in the communication with students that takes places after classes. In terms of pragmatics, it is: lack of professional skills and respect for work, especially lack of care concerning the quality of knowledge passed to students, schematic teaching, and within ethics – lack of moral standards, especially linguistic aggression of teachers towards the youth.